Clinical Applications of 3D Specimen Scanning and Margin Mapping in Musculoskeletal Oncology: A 36 Patient Case Series - Riley S. Gilbertson; Sakshi Krishna; Joaquin Austerlitz; Andreja Radevic; Michael J. Colello; Alexander N. Perez; Reena Singh; Jennifer L. Halpern; Herbert S. Schwartz; Michael C. Topf; Joshua M. Lawrenz; Daniel J. Johnson (Journal of Surgical Oncology, 2026)
ABSTRACT Background Text‐based pathology reports inadequately communicate complex three‐dimensional (3D) relationships in musculoskeletal oncology, potentially contributing to errors in re‐resection and adjuvant treatment planning. While our prior 7‐case pilot study established technical feasibility, the scalability of this workflow and its utility as a platform for further innovation have not been demonstrated. Methods We conducted a prospective implementation study of 36 musculoskeletal oncology specimens at a tertiary sarcoma center between April 2023 and November 2025. Specimens underwent ex vivo 3D scanning using a structured light scanner, followed by virtual annotation using computer‐aided design software to mirror the standard‐of‐care grossing process and create visual pathology reports (VPRs). The primary outcome was systematic implementation without disrupting standard processing. Secondary outcomes included platform‐derived applications: augmented reality (AR)‐guided re‐resection, 3D margin heat maps, and 3D wound‐bed scans. Results All 36 specimens were scanned and mapped (21 soft tissue, 13 bone, 2 metastatic; median greatest specimen dimension 12.7 cm). Positive margins occurred in 13.9% ( N = 5) of cases. VPRs were presented in multidisciplinary tumor boards in three of these five cases. AR guidance was implemented in eight staged‐resection cases ( N = 4 for positive margin re‐resection, N = 4 for pre‐reconstruction planning), 3D heat maps were created for eight cases, and intraoperative wound bed scanning was piloted once. Discussion/Conclusion 3D specimen scanning and virtual mapping are scalable workflows providing a permanent visual record of resected specimens and functioning as a foundational platform for novel interventions. AR‐guided surgery and 3D heat mapping demonstrate potential paradigm shifts from static reporting to dynamic, visual pathologic reporting and surgical guidance.